1999
DOI: 10.1038/sj.bjc.6690628
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in the p53 gene and prognosis in breast cancer: a meta-analysis

Abstract: Summary Many studies have investigated the association between alterations in the p53 gene and clinical outcome of breast cancer, and most investigators have reported poorer overall and disease-free survival (as indicated by a relative hazard (RH) greater than one) in breast cancer cases with somatic mutations in p53. However, different studies have produced widely differing RH estimates, ranging from no risk (RH = 1) to a relative hazard of 23, and not all of these results have been statistically significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
2
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(198 citation statements)
references
References 33 publications
13
173
2
10
Order By: Relevance
“…Two hundred and forty-eight women with breast cancer and available tumor samples were studied and the mean follow-up time was 55 months with a range of 12-140 months. Similar to previously published results (Pharoah et al, 1999), the 48 women with a mutated p53 gene (exons 5-8) in their tumors showed a significant increase in the risk ratio of death of 1.88-fold [95% CI 1.03-3.41, P ¼ 0.039] compared to the 200 women who retained a wild-type p53 gene. Interestingly, when the patients were analysed separately based on their SNP309 status, it became clear that the increased risk ratio of death associated with mutant p53 was only found in those women T/T in genotype and not in individuals who carry the G-allele of SNP309.…”
Section: Tumor Genetics: the P53 Mutational Statussupporting
confidence: 88%
“…Two hundred and forty-eight women with breast cancer and available tumor samples were studied and the mean follow-up time was 55 months with a range of 12-140 months. Similar to previously published results (Pharoah et al, 1999), the 48 women with a mutated p53 gene (exons 5-8) in their tumors showed a significant increase in the risk ratio of death of 1.88-fold [95% CI 1.03-3.41, P ¼ 0.039] compared to the 200 women who retained a wild-type p53 gene. Interestingly, when the patients were analysed separately based on their SNP309 status, it became clear that the increased risk ratio of death associated with mutant p53 was only found in those women T/T in genotype and not in individuals who carry the G-allele of SNP309.…”
Section: Tumor Genetics: the P53 Mutational Statussupporting
confidence: 88%
“…For breast cancer, a meta-analysis of 11 studies involving 2319 unselected cases found a relative risk (RR) for worse survival associated with p53 mutation of 2.0 (95% CI: 1.7-2.5). 51 The RR for node-negative breast cancers (1.7, 95% CI: 1.2-2.3) was lower than that for node-positive cases (2.6, 95% CI: 1.7-3.9) but remained significant. TP53 mutation also showed independent prognostic value for worse survival in nonadjuvant (RR ¼ 2.2, 95% CI: 1.2-4.2) and adjuvant treated (RR ¼ 2.0, 95% CI: 1.3-3.1) breast cancer patients.…”
Section: Prognostic Significance Of P53 Mutation In Cancer -Does It Amentioning
confidence: 82%
“…These findings suggested the XEDAR as a p53-induced regulator of anoikis C Tanikawa et al inhibitory effects of XEDAR on cell adhesion and/or motility. The presence of the p53 mutation was indicated to be significantly correlated with metastasis and poor prognosis of various cancers (Diez et al, 2000;Pharoah et al, 1999 XEDAR as a p53-induced regulator of anoikis C Tanikawa et al key role in the metastatic property of p53-mutated cancer. We then carried out a colony formation assay in soft agar using cancer cell lines with low or absent expression of XEDAR (DLD-1, HCT116, SW480, SW620 and H1299 cells) and found that XEDAR could suppress anchorage-independent tumor cell growth (Figure 3c).…”
Section: Role Of Xedar In Anoikismentioning
confidence: 99%